"I Need to Do This on My Own" Resilience and Self-Reliance in Urban At-Risk Youths. Issue 10 (2nd October 2020) - Lenkens, Margriet; Rodenburg, Gerda; Schenk, Loïs; Nagelhout, Gera E.; Van Lenthe, Frank J.; Engbersen, Godfried; Sentse, Miranda; Severiens, Sabine; Van De Mheen, Dike
ABSTRACT: This qualitative study investigates urban at-risk youths' perspectives on their multiproblem situations and explores their needs for support. Semi-structured interviews were conducted with 23 at-risk youths with varied (externalizing) problems and risk factors. The data analysis was carried out using an inductive thematic approach. Four main themes emerged: desistance from delinquent behavior, need for self-reliance, negative experiences in social relationships and need for support. The participants indicated a strong need to be(come) self-reliant, which was visible in their statements on independence, coping with problems and reluctance to seek or accept help, also regarding desistance from crime. For some, this need for self-reliance seemed to be accompanied by distrust of others, which appeared related to previous negative experiences in social interactions. The participants seemed more open to support coming from someone with similar characteristics or experiences. The findings suggest that in helping at-risk youths, a delicate balance should be sought between stimulating autonomy and providing the necessary resources for support. A focus on strengthening factors that foster resilience is recommended. Future research could investigate the possible benefits of perceived similarity between youths and their care providers.